2020
DOI: 10.1016/j.clinms.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for score assignment to characterize biological processes from mass spectral analysis of serum

Abstract: Highlights Biological process-associated scores generated from mass spectrometry of serum. Scores demonstrated acceptable levels of reproducibility. Scores associated with biological processes and clinical outcome in cancer patients. Possible application to biomarker studies for treatment or monitoring of disease. Multiple biological processes assessed from 3 µL of serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The abundances of multiple serum proteins are correlated with VS classification, including C-reactive protein (CRP), interleukin-6 (IL-6), serum amyloid A (SAA), the cytokeratin 19 fragment CYFRA 21-1, insulin-like growth factor 2 (IGF-2), and osteopontin [6] . Set enrichment analysis techniques have shown that VS classification is associated with acute phase response [6] , [7] , [8] , acute inflammatory response, and complement activation [7] , [8] . It is well known that truncated proteoforms of serum amyloid A are present in the mass/charge range of some of the VS features in Table 1 [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…The abundances of multiple serum proteins are correlated with VS classification, including C-reactive protein (CRP), interleukin-6 (IL-6), serum amyloid A (SAA), the cytokeratin 19 fragment CYFRA 21-1, insulin-like growth factor 2 (IGF-2), and osteopontin [6] . Set enrichment analysis techniques have shown that VS classification is associated with acute phase response [6] , [7] , [8] , acute inflammatory response, and complement activation [7] , [8] . It is well known that truncated proteoforms of serum amyloid A are present in the mass/charge range of some of the VS features in Table 1 [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The abundances of multiple serum proteins are correlated with VS classification, including C-reactive protein (CRP), interleukin-6 (IL-6), serum amyloid A (SAA), the cytokeratin 19 fragment CYFRA 21-1, insulin-like growth factor 2 (IGF-2), and osteopontin [6]. Set enrichment analysis techniques have shown that VS classification is associated with acute phase response [6][7][8], acute inflammatory response, and complement activation [7,8]. Indeed, it is well known that truncated proteoforms of serum amyloid A are present in the mass/charge range of some of the VS features in Table 1 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent performance resulted, as diagnostic peaks became harder to differentiate from noise despite enhanced sensitivity. A modification of data-acquisition settings to discriminate noise-obscured biomarkers present in unfractionated human serum, called 'deep-MALDI' , was patented in 2013 for use with the MBT and involves using > 20,000 laser shots during data collection to produce superior spectra 25 . Later, the same researchers reported improved biomarker discrimination when applying even greater amounts of spectrum averaging, of 100,000,000 laser shots or more, in some of their published data 26 .…”
mentioning
confidence: 99%